2015
DOI: 10.1111/arcm.12208
|View full text |Cite
|
Sign up to set email alerts
|

Technical Studies on the Bronze Age Metal Artefacts from the Graveyard of Deh Dumen, South-Western Iran (Third Millennium BC)

Abstract: During the excavations of the graveyard at the site of Deh Dumen in south-western Iran, 15 graves from the Early/Middle Bronze Age were uncovered that contained a variety of metallic artefacts. This paper reports on the analysis of nine metal artefacts, including eight broken vessels and a decorative strip that covered the handle of a dagger. The ICP-MS results showed that the bodies of the vessels are made of tin bronze alloy with variable amounts of tin, while the internal piece of the base of one vessel is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…It is important to note that all artefacts from Sangtarashan analysed are vessels (or vessel accessories such as pins, handles and spouts) and tin concentrations vary among the samples from 1.78 to 14.5 wt%, showing no correlation between tin concentration and artefacts typology. This variability was observed previously in other copper-base artefacts from prehistoric Iran, including Marlik and Deh Dumen (Oudbashi and Hessari, 2017;Oudbashi et al, 2016c), and particularly in vessels from War Kabud and Sangtarashan (Oudbashi, 2019b).…”
Section: Luristan Bronzes: Technology and Provenancesupporting
confidence: 75%
See 1 more Smart Citation
“…It is important to note that all artefacts from Sangtarashan analysed are vessels (or vessel accessories such as pins, handles and spouts) and tin concentrations vary among the samples from 1.78 to 14.5 wt%, showing no correlation between tin concentration and artefacts typology. This variability was observed previously in other copper-base artefacts from prehistoric Iran, including Marlik and Deh Dumen (Oudbashi and Hessari, 2017;Oudbashi et al, 2016c), and particularly in vessels from War Kabud and Sangtarashan (Oudbashi, 2019b).…”
Section: Luristan Bronzes: Technology and Provenancesupporting
confidence: 75%
“…This is observed in artefacts from Early Bronze Age Luristan graveyards such as Kalleh Nisar and Bani Surmeh, Susa dated to period IVa (second half of third millennium BCE) and at Godin Tepe III:6 (ca. 2600-2400 BCE), as well as the Bronze Age graveyard of Deh Dumen, south-western Iran (Frame, 2010;Fleming et al, 2005;Malfoy and Menu, 1987;Oudbashi et al, 2016c). It is worth noting that these tin bronze artefacts occurred alongside arsenical copper artefacts, which were common during the Early and Middle Bronze Age of western and south-western Iran.…”
Section: Elemental Compositionmentioning
confidence: 98%
“…Our work has suggested that Fe may sometimes be included in the more stable readings typically associated with the alloy, although this must be done carefully. Destructive analyses have indicated that Fe does often appear in higher quantities in the upper layers of patinas on many bronze objects, suggesting it may originate in the soil and not the alloy in some contexts [59]. However, in our samples, Fe variations followed patterns similar to other alloy-based elements with a general decrease over time and no significant variation due to location.…”
Section: Discussionmentioning
confidence: 51%
“…The variety of tin content proves that the objects have not been made by a particular alloy proportion to reach a homogenous bronze composition such as adding a distinct amount of tin to copper and melting them, but an uncontrolled process is used to produce tin bronze alloy, such as co-smelting, cementation, recycling or smelting copper-tin containing ores [3,12,19,20]. The variability of tin content is commonplace in the study of the Iron Age bronze objects of Iran, especially in Luristan bronzes.…”
Section: Alloy Compositionmentioning
confidence: 99%
“…In fact, some copper sulphide didn't transform to metallic copper during the smelting and will be evident as grey-green inclusions in the bronze microstructure. It should be noted that these Cu-S inclusions are observed in many copper and bronze objects from the Bronze Age to the Iron Age of western and northern Iran [8,12,20,23]. Presence of low amount of iron is most probably due to the presence of iron in smelted copper ore, in the form of iron sulphides or use of an iron-copper sulphide such as chalcopyrite [22].…”
Section: Microstructurementioning
confidence: 99%